Dismantling weight stigma in eating disorder treatment: Next steps for the field - McEntee, Mindy L.; Philip, Samantha R.; Phelan, Sean M. (Frontiers in Psychiatry, 2023)
The authors posit current guidelines and treatment for eating disorders (EDs) fail to adequately address weight stigma and the underlying contextual history of racism, sexism, and classism in the field. While reliance on studies conducted among predominantly white, middle-to-upper class women is not a new criticism, there has been little conversation about ED treatment emerging from a weight-centric medical paradigm. The social devaluation and denigration of higher-weight individuals cuts across nearly every life domain and is associated with negative physiological and psychosocial outcomes, mirroring the harms attributed to weight itself. Maintaining focus on weight in ED treatment can intensify weight stigma among patients and providers, leading to increased internalization, shame, and poorer health outcomes. Stigma has been recognized as a fundamental cause of health inequities. With no clear evidence that the proposed mechanisms of ED treatment effectively address internalized weight bias and its association with disordered eating behavior, it is not hard to imagine that providers’ perpetuation of weight bias, however unintentional, may be a key contributor to the suboptimal response to ED treatment. Several reported examples of weight stigma in ED treatment are discussed to illustrate the pervasiveness and insidiousness of this problem. The authors contend weight management inherently perpetuates weight stigma and outline steps for researchers and providers to promote weight inclusive care (targeting health behaviors rather than weight itself) as an empirically supported alternative capable of addressing many of the social injustices in the history of this field.